Patient and family engagement: a survey of US hospital practices - Herrin, Jeph (BMJ Qual Saf, 2016)
BACKGROUND: Patient and family engagement (PFE) in healthcare is an important element of the transforming healthcare system; however, the prevalence of various PFE practices in the USA is not known. OBJECTIVE: We report on a survey of hospitals in the USA regarding their PFE practices during 2013–2014. RESULTS: The response rate was 42%, with 1457 acute care hospitals completing the survey. We constructed 25 items to summarise the responses regarding key practices, which fell into three broad categories: (1) organisational practices, (2) bedside practices and (3) access to information and shared decision-making. We found a wide range of scores across hospitals. Selected findings include: 86% of hospitals had a policy for unrestricted visitor access in at least some units; 68% encouraged patients/families to participate in shift-change reports; 67% had formal policies for disclosing and apologising for errors; and 38% had a patient and family advisory council. The most commonly reported barrier to increased PFE was ‘competing organisational priorities’. SUMMARY: Our findings indicate that there is a large variation in hospital implementation of PFE practices, with competing organisational priorities being the most commonly identified barrier to adoption.